KONTESTASI NARASI CBT YANG BERKELANJUTAN PADA KOMPLEKSITAS EKOSISTEM DESA WISATA - Chandra Yudha Satriya; Heni Indrayani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This research is based on the argument that the model of community development as complexity is very different. Because it takes a bottom-up approach, which is seen from the interactive (relational) discourse or view between individuals and society in an increasingly complex environment, and seeing how the two influence each other. This study aims to analyze and describe the discourse of the Community-Based Tourism (CBT) program in the Karanganyar tourist village, Magelang district. This research uses a qualitative approach and data collection is done through in-depth interviews, media monitoring, and FGD. The results of the study show that the CBT narrative has been interpreted and understood differently, and this depends on the structural position of each element, be it the government, strategic partners, or the tourism village community. Meanwhile, the government interprets the concept of CBT as the domination of economic and political interests. This study enriches communication studies on unequal power relations between development elements and recommendations for community empowerment through CBT.